Development and fabrication on the oil palm fiber/ glass reinforced in aluminium composite laminates - Sia, Charlie Chin Voon (Universiti Malaysia Sarawak, UNIMAS, 2009)
An experiment has been carried out to produce higher mechanical performances and lower cost composite material to reduce the usage of aluminium. This research involves development, fabrication, mechanical testing and fracture analysis of the new type of composite materials. Using laminate concept where glass fiber mat and oil palm empty fruit brunch fiber (OPEFBF) were selected as the reinforcement.